2005
DOI: 10.1007/s00428-005-1274-7
|View full text |Cite
|
Sign up to set email alerts
|

DCIS, cytokeratins, and the theory of the sick lobe

Abstract: We postulate that ductal carcinoma in situ (DCIS), and consequently breast carcinoma in general, is a lobar disease, as the simultaneously or asynchronously appearing, often multiple, in situ tumor foci are localized within a single lobe. Although the whole lobe is sick, carrying some form of genetic instability, the malignant transformation of the epithelial cells may appear localized to a part or different parts of the sick lobe at the same time or with varying time difference. It may be confined to terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
79
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 31 publications
4
79
1
3
Order By: Relevance
“…Defining the extent by the dimensions of the involved area also proved to be a sensitive approach in our previous study regarding in situ breast carcinomas, showing a nearly 10-fold difference in the local recurrence rate between extensive (area > 2 cm) and nonextensive ductal in situ breast carcinomas. 13 Our hypothesis, the theory of the sick lobe, 13 defines breast carcinoma as a lobar disease originating in a single breast lobe in the majority of cases. In situ carcinoma may appear in the ducts and the lobules of the sick lobe simultaneously in large areas or with time differences involving small parts of it.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Defining the extent by the dimensions of the involved area also proved to be a sensitive approach in our previous study regarding in situ breast carcinomas, showing a nearly 10-fold difference in the local recurrence rate between extensive (area > 2 cm) and nonextensive ductal in situ breast carcinomas. 13 Our hypothesis, the theory of the sick lobe, 13 defines breast carcinoma as a lobar disease originating in a single breast lobe in the majority of cases. In situ carcinoma may appear in the ducts and the lobules of the sick lobe simultaneously in large areas or with time differences involving small parts of it.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the well-recognized importance of the distribution of cancer within the breast for optimizing breast-conserving surgery, 4 there are conflicting results in the related literature regarding the significance of breast cancer multifocality, depending on the methodologic limitations and the various definitions used lacking a wide international consensus. [1][2][3][5][6][7][8][9][10][11][12][13][14] The diffuse growth pattern of some highly aggressive breast carcinomas 10 remains mainly unrecognized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility for the wide spreading of this lesion is that micropapillary structures may develop simultaneously on a large area of a breast lobe. 40 The extensive nature of the micropapillary in situ cancer was first reported by Patchefsky et al 22 and confirmed by other authors. 20,21 Bellamy et al 32 described that micropapillary growth, more likely than other growth patterns of in situ carcinoma, involves multiple quadrants, regardless of nuclear grade or necrosis.…”
Section: Discussionmentioning
confidence: 59%